METHODOLOGY FOR ORGANIZING ELEMENTARY SCHOOL EDUCATION CLASSES (American Journal of Interdisciplinary Research and Development, 2024)
This article will review reviews and reflections on the methodology of organizing parenting lessons in elementary school. The importance of elementary education in shaping the foundation for a child's future cannot be overstated. A well-structured and carefully thought-out methodology in organizing these early classes is crucial in promoting cognitive, emotional, and social development. As children navigate this formative phase of their education, the right teaching strategies can ignite their curiosity, build essential life skills, and cultivate a lifelong passion for learning.